2019
DOI: 10.1111/tra.12640
|View full text |Cite
|
Sign up to set email alerts
|

TRAPPC11 functions in autophagy by recruiting ATG2B‐WIPI4/WDR45 to preautophagosomal membranes

Abstract: TRAPPC11 has been implicated in membrane traffic and lipid‐linked oligosaccharide synthesis, and mutations in TRAPPC11 result in neuromuscular and developmental phenotypes. Here, we show that TRAPPC11 has a role upstream of autophagosome formation during macroautophagy. Upon TRAPPC11 depletion, LC3‐positive membranes accumulate prior to, and fail to be cleared during, starvation. A proximity biotinylation assay identified ATG2B and its binding partner WIPI4/WDR45 as TRAPPC11 interactors. TRAPPC11 depletion phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 79 publications
(212 reference statements)
4
53
0
Order By: Relevance
“…Recent work has shown that the ESCRT‐III component CHMP2A regulates the separation of inner and outer phagophore membranes , and more recently, VPS37A is essential for phagophore closure . In addition to the ESCRT‐III machinery, TRAPPC11, a member of TRAPP complexes involved in membrane trafficking, has been shown to recruit ATG2B‐WIPI4 to phagophores in an ATG9A‐dependent manner . The depletion of TRAPC11 results in a phenotype similar to that of ATG2A/B DKO and ATG2A‐mLIR .…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that the ESCRT‐III component CHMP2A regulates the separation of inner and outer phagophore membranes , and more recently, VPS37A is essential for phagophore closure . In addition to the ESCRT‐III machinery, TRAPPC11, a member of TRAPP complexes involved in membrane trafficking, has been shown to recruit ATG2B‐WIPI4 to phagophores in an ATG9A‐dependent manner . The depletion of TRAPC11 results in a phenotype similar to that of ATG2A/B DKO and ATG2A‐mLIR .…”
Section: Resultsmentioning
confidence: 99%
“…The wide range of TRAPPopathies associated with the human TRAPC11 mutations include, among others, muscular dystrophy, myopathy, and liver disease (Sacher et al, 2019) and point toward yet-undiscovered functions of the AtTRAPPC11/ROG2 in plant physiology. The role of human TRAPPC11 upstream of autophagosome formation was recently demonstrated (Stanga et al, 2019); a similar function warrants exploration in plant cells, especially under biotic and abiotic stress.…”
Section: Loss Of Attrappc11 Affects Root Growth and Plant Stress Respmentioning
confidence: 85%
“…Purification with Trs120-S showed that in addition to the 'core TRAPP hetero-heptamer' and the TRAPPII-specific subunits Trs120, Trs130 and Trs65, TRAPPII contains Tca17 ( Fig 1D and 1E), which was missing in the single particle EM yeast TRAPPII structure [30], but is a demonstrated yeast TRAPPII component [8,9]. The finding that TRAPPC11, TRAPPC12 and TRAPPC13 are absent from TRAPPII suggested that they belong to TRAPPIII, as in mammalian TRAPPs) [31][32][33][34], which is confirmed below. Thus, A. nidulans TRAPPs resemble those of metazoans to a greater extent than those of S. cerevisiae.…”
Section: Composition Of a Nidulans Trappsmentioning
confidence: 99%